CASE REPORT : OLFACTORY GROOVE MENINGIOMA (Lombok Health And Science Journal, 2024)
AbstractBackground: Olfactory Groove Meningiomas (OGM) are a rare cause of olfactory dysfunction. OGMs are benign, slow-growing tumors that cause non-specific symptoms, such as headaches, olfactory impairment, and psychiatric symptoms, such as depression, personality changes, decreased cognitive function, visual problems, or seizures.Aim: In this case report we would like to discuss about a rare case of olfactory groove meningioma with non-spesific symptoms presented in 47-year old female patientCase report: A 47-year old female with progressive blurred vision in the right eye for 3 months. Negative light perception in the right eye and fundus of the right eye indicated papillary atrophy. The direct and indirect light reflexes were negative in the right eye. We found Strong homogenous contrast enhancement extraaxial lesion accompanied by multiple dural tails in the left frontal convexity UK approximately 3.2 x 2.8 x 3.1 cm, Tuberculum sellae approximately 2.7 x 2.9 x 3 cm. Cranial decompression, frontal bone reconstruction, and tumor removal were performed. It was found that there was microcystic growth of tumor tissue, consisting of proliferation of meningoethelial cells, round to oval nuclei, smooth chromatin, visible intranuclear inclusionsDiscussion: OGM is a rare, benign tumor. Female patients were more likely to develop OGM than male patients. The ciliary ganglion of cranial nerve III may be affected by compression of the tumor, resulting in the absence of direct and indirect pupillary reflexes in the affected eyes.Conclusion: OGM is a slow-growing tumor that does not show significant symptoms at an early stage, making early detection difficult.Keyword: Olfactory Groove Meningioma, Blurred Vision, Meningioma